Synthesis and Antiproliferative Activity of Novel Heterocyclic Indole-Trimethoxyphenyl Conjugates - Michael M. Cahill; Kevin D. O'Shea; Larry T. Pierce; Hannah J. Winfield; Kevin S. Eccles; Simon E. Lawrence; Florence O. McCarthy (MDPI AG, 2017)
The synthesis and biological evaluation of a series of novel heterocyclic indole derivatives is described. The consolidation of the combretastatin and bisindolylmaleimide templates towards the inclusion of a novel heterocyclic ring proffered a versatile pharmacophore with which to pursue chemical diversification. Given literature precedent, maleimide was initially investigated in this role and the bioactivity assessed by measurement of NCI-60 cell panel growth. Subsequently, a range of 5-aminopyrazoles was designed and developed to explore the specific effect of heterocycle hydrogen bonding on cell growth. The unique electronic nature of the 5-aminopyrazole moiety allowed for regiospecific monosubstitution on different sites of the ring, such as thiourea substitution at the N(1) position for derivative 45 or trifluoroacetylation on the 5-amino position for 43. Further derivatisation led to the ultimate development of bicyclic pyrazolotriazinedione 41 and pyrimidine 42 systems. The antiproliferative activities of these 3,4-diaryl-5-aminopyrazoles were assessed using the NCI-60 cell screen, disclosing the discovery of distinct selectivity profiles towards a number of cell lines, such as SNB-75 CNS cancer, UO-31 and CAKI-1 renal cancer cells. A series of DNA topological assays discounted the interaction with topoisomerase II as a putative mechanism of action.